High Triatoma brasiliensis densities and Trypanosoma cruzi prevalence in domestic and peridomestic habitats in the State of Rio Grande do Norte, Brazil: The source for Chagas disease outbreaks? - Lilioso, Mauricio (2018)
A total of 2,431 Triatoma brasiliensis were collected from 39 populations of Paraíba (PB) and Rio Grande do Norte (RN) states, Brazil. In PB, Trypanosoma cruzi infection was not detected in either peridomestic or domestic vector populations. In contrast, in RN, T. brasiliensis was detected with high parasite prevalence in these ecotopes (30.7-40.0%). Moreover, peridomicile insect population densities were more than double the average densities of all other settings evaluated (19.17 versus < 8.94 triatomine/man-hour). Genotyped parasites evidenced a mix of T. cruzi lineages circulating in both peridomestic and sylvatic populations. Although vector control efforts have dramatically decreased Chagas disease transmission to humans, recent outbreaks have been detected in four municipalities of RN state. Our results clearly evidence a worrisome proximity between infected vectors and humans in RN. Indeed, finding of infected T. brasiliensis inside homes is routinely recorded by local vector control surveillance staff around the outbreak area, challenging the current and conventional view that vector transmissions are controlled in northeastern Brazil. This scenario calls for strengthening vector control surveillance and interventions to prevent further Chagas transmission, especially in RN State.